Accidental Oleandrum (Nerium Oleander L.) Ingestion: Anatomo-Pathological consequences in livestock species - Tinelli, A; Passantino, G; Perillo, A; Zizzo, N (Journal of the Hellenic Veterinary Medical Society, 2023)
The oleander (Nerium oleander L.) is a flowering and evergreen shrub or small tree, belonging to the Dogbane family, cultivated as ornamental plants in gardens and public city areas. These plants, distributed originally in Asia and Mediterranean area, grow in many parts of the world, particularly in warm temperate and subtropical regions. Oleander is considered noxious weed and its toxicity has been known since ancient times. All parts of plants, including stems, leaves, young shoots, flowers, nectar, sap and products induced by combustion are toxic. The poisoning effects of plant induced sever negative changes especially in the heart, also in the lung, in the liver and in the kidney. Accidental and experimental cases of oleander poisonings have been described in several species. Several cases of accidental ingestion in human and animals have been reported from across the world. Therefore, this review summarizes the main anatomo-pathological effects found in livestock species after accidental oleandrum poisoning.